Orbito-Frontal Cortex Volumes in Panic Disorder - Atmaca, Murad; Yildirim, Hanefi; Gurok, M. Gurkan; Akyol, Muammer (Korean Neuropsychiatric Assoc, 2012)
Objective Given the association between the pathophysiology of panic disorder and prefrontal cortex function, we aimed to perform a volumetric MRI study in patients with panic disorder and healthy controls focusing on the in vivo neuroanatomy of the OFC. Methods Twenty right-handed patients with panic disorder and 20 right-handed healthy control subjects were studied. The volumes of whole brain, total white and gray matters, and OFC were measured by using T1-weighted coronal MRI images, with 1.5-mm-thick slices, at 1.5T. In addition, for psychological valuation, Hamilton Depression Rating (HDRS) and Panic Agoraphobia Scales (PAS) were administered. Results Unadjusted mean volumes of the whole brain volume, total white and gray matter were not different between the patients and healthy controls while the patient group had significantly smaller left (t=-6.70, p<0.0001) and right (t=-5.86, p<0.0001) OFC volumes compared with healthy controls. Conclusion Our findings indicate an alteration of OFC morphology in the panic disorder and suggest that OFC abnormalities may be involved in the pathophysiology of panic disorder. Psychiatry Investig 2012;9:408-412
Keywords: Panic disorder; Volume; OFC; MRI